Application Aware Multicasting in VPLS Networks. - Kweli,Allan (Department of Electrical Engineering, 2024)
Enterprise customer demand for business class Ethernet service offerings, over the years, has steadily increased. More so, the demand for high throughput coupled with efficient utilization of the available bandwidth. This has driven service providers to seek more reliable means of delivering services to their customers. As businesses expand both financially and geographically service providers have deployed Wide Area Networks (WANs) to deliver Ethernet services to their customers. However the deployment of such networks raises issues related to the cost and scalability of the network deployment. Furthermore the efficiency, in relation to resource utilization, of the network is a major concern to both the SP and the client. Ethernet services provided by a Virtual Private LAN Service (VPLS) network provide scalability, resilience and efficient utilization of the existing network resources. The objectives of this thesis are to investigate how VPLS can offer on-demand business class Ethernet services while being consistent with the core network organization. Furthermore this research aims to develop efficient bandwidth utilization in a Point-to-Multipoint VPLS network using Multiprotocol Label Switching (MPLS) as a transport protocol. MPLS is a Layer 2.5 transport protocol that encapsulates and labels frames from their sources to their destinations. MPLS uses labels to identify the frame destination and in so doing reduces the overall bandwidth when IP headers are used. MPLS facilitates the deployment of VPLS networks, thus VPLS relies on MPLS as its transport protocol. VPLS networks offer emulated Ethernet services, are scalable and are not restricted by geographical dispersion of the customer sites. VPLS networks over MPLS also offer efficient utilization of the networks' bandwidth through mechanisms such as multicast awareness, auto-bandwidth allocation, signaling and auto-discovery. From the mentioned mechanisms, this thesis aims at setting up a VPLS network in a virtualized environment. The reason being, it is cost effective and line with archiving cost efficiency. In the VPLS network, the preferred signaling protocol is Label Distribution Protocol (LDP) as it is essential in the establishment of the MPLS backbone network. The VPLS pseudowires are dynamically created using the Border Gateway Protocol (BGP) protocol. The BPG protocol also ensures scalability, using route-reflect routers in the network. The auto- discovery of peering nodes in the VPLS network is achieved using the BGP protocol. Multicast vii awareness is achieved by configuring separate VPLS instances. Therefore the traffic is not flooded into the network but rather forwarded to members belonging to the same VPLS instance so the existing bandwidth is efficiently utilized. By using MPLS traffic engineered (MPLS- TE)tunnels; the auto-bandwidth mechanism is implemented. Auto-bandwidth control over the MPLS-TE tunnels ensures improved utilization of the available tunnel bandwidth. As mentioned before, the VPLS network is in a virtualized environment. The network routers are based on the Mikrotik routerOS. The routerOS is a standalone operating system based on the Linux v2.6 kernel. The customer sites created have server and client machines, all of which have been virtualized.